2019
DOI: 10.3390/agronomy9090546
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Spraying 6-BA in the Late Jointing Stage on the Fertile Floret Development and Grain Setting in Winter Wheat

Abstract: Wheat yield is largely determined by the grains per spike, which in turn is related to the fertile floret development prior to anthesis. The aim of this study was to assess the physiological mechanism of exogenous 6-benzylaminopurine (6-BA) on fertile floret development and grain setting characteristics by foliar application in winter wheat. Field experiments were conducted during the 2016–2017 and 2017–2018 growing seasons in China. Two foliar spraying applications with water (S0) and 6-BA (S1) were applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…However, there is a negative correlation between auxin concentration and the number of fertile florets at the abortion stage. Adding exogenous 6-benzylaminopurine (6-BA, a synthetic CK) during the abortion phase increased the CK level, reduced the auxin level, decreased the number of floret abortions, and increased spike dry weight ( Li et al , 2019 ). Thus, increasing CK levels in spikes during the floret abortion phase results in increased grain number, for example, by decreasing cytokinin oxidase activity that catalyses the degradation of CK ( Bartrina et al , 2011 ; Zhang et al , 2011 ).…”
Section: Wds From the Onset Of Stem Elongation To Anthesismentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is a negative correlation between auxin concentration and the number of fertile florets at the abortion stage. Adding exogenous 6-benzylaminopurine (6-BA, a synthetic CK) during the abortion phase increased the CK level, reduced the auxin level, decreased the number of floret abortions, and increased spike dry weight ( Li et al , 2019 ). Thus, increasing CK levels in spikes during the floret abortion phase results in increased grain number, for example, by decreasing cytokinin oxidase activity that catalyses the degradation of CK ( Bartrina et al , 2011 ; Zhang et al , 2011 ).…”
Section: Wds From the Onset Of Stem Elongation To Anthesismentioning
confidence: 99%
“…cytokinin oxidase/dehydrogenase, CKX)] enzymes. The grain sink strength of the spike meristem could therefore be enhanced by altering CK homeostasis through the up-regulation or down-regulation of these enzymes, respectively, to coordinate growth and floret fertility ( Li et al , 2019 ). While there has been speculation on a possible trade-off between fruiting efficiency and spike dry weight at anthesis (see above; Link 10, Fig.…”
Section: Wds From the Onset Of Stem Elongation To Anthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous application of 6-BA effectively alleviated the adverse effects of waterlogging on maize by increasing the leaf area index and chlorophyll content, reducing the MDA content, maintaining the stability of chloroplast ultrastructure (Ren et al, 2017), and reducing the ABA content (Hu et al, 2022). Exogenous 6-BA application during the fertile florets abortion stage of wheat increased the number of florets and number of grains by primarily suppressing the number of degenerated and aborted florets, which result in a further increase in grain yield (Li et al, 2019). Yuan et al (2014) reported that soaking maize seeds by 6-BA could alleviate the physiological damage under drought stress.…”
Section: Introductionmentioning
confidence: 99%